1996
DOI: 10.1017/s0016672300033735
|View full text |Cite
|
Sign up to set email alerts
|

An additional type of male sterility and inherited urinary obstruction in mice with thet-haplotypeth7

Abstract: SummaryThe t-complex on mouse chromosome 17 results in transmission ratio distortion in males heterozygous for complete haplotypes, and sterility in those homozygous for semi-lethal or doubly heterozygous for complementing lethal haplotypes. This sterility is due to inability of spermatozoa to fertilize. The haplotype th7 is an unusual laboratory-derived haplotype, postulated to carry a small duplication of t chromatin. Males heterozygous for th7 show a new form of sterility, apparently due to failure to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Because T is expressed throughout the notochord, it is possible for the phenotypic manifestation of a mutation to occur anywhere along the vertebral column. Indeed, in mice, T mutations affect not only the tail but also more anterior vertebral segments, ( (26,27)) spinal cord, ( (26,28)) genitourinary system, ( (26,29)) and heart. ( (30,31)) Other investigators have reported the association of a C to T transition in intron 7 of T and increased risk of neural tube defects, ( (32–34)) but this finding has not been uniformly reproduced. ( (35–37)) Thus, the potential range of mutant T phenotypes must be broadened to include neural tube defects, as well as CVMs. Moreover, it is desirable to account for the absence of a clinical phenotype in the unaffected parents of our three c.1013C>T CVM subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Because T is expressed throughout the notochord, it is possible for the phenotypic manifestation of a mutation to occur anywhere along the vertebral column. Indeed, in mice, T mutations affect not only the tail but also more anterior vertebral segments, ( (26,27)) spinal cord, ( (26,28)) genitourinary system, ( (26,29)) and heart. ( (30,31)) Other investigators have reported the association of a C to T transition in intron 7 of T and increased risk of neural tube defects, ( (32–34)) but this finding has not been uniformly reproduced. ( (35–37)) Thus, the potential range of mutant T phenotypes must be broadened to include neural tube defects, as well as CVMs. Moreover, it is desirable to account for the absence of a clinical phenotype in the unaffected parents of our three c.1013C>T CVM subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Since expression of T is distributed throughout the notochord, it is possible for the phenotypic manifestation of a mutation to occur anywhere along the vertebral column. This is exemplified by the observation that T mutations in mice affect not only the tail, but also more anterior vertebral segments, 124,125 spinal cord, 124,126 genitourinary system, 124,127 and heart 128,129 . An association between a C to T transition in intron 7 of T and increased risk of neural tube defects 130–132 has been reported by some investigators, but this finding has not been uniformly reproduced 133–135 .…”
Section: Klippel−feil Syndromementioning
confidence: 99%
“…Therefore, alterations in methylation may significantly affect embryonic development (Rogers et al, 1994). Evidence of the genetic role in growth and reproductive development has been described (Lyon, 1996) and influence of heredity on body size has been reported (de Table 3-5-AZA-2′-Deoxycytidine F1 reproductive parameters (3 months of age) Castro, 1993). In addition, maternal factors play a role in the development of the exaggerated appetite for some specific nutrients (Erkadius et al, 1996).…”
Section: Discussionmentioning
confidence: 99%